The faith-based welfare state, 2001-2017 - Jakubek, Joseph Thomas (Kansas State University, 2019)
This qualitative historical study seeks to describe the institutionalization of Faith-Based Initiatives within structures of the federal government from 2001-2017. Through an analysis of the strategies and goals adopted by the Office of Faith-Based and Community Initiatives and the Office of Faith-Based and Neighborhood Partnerships, this study illuminates aspects of state-centered theory as well as theoretical insights from the sociology of religion. The historical case study provided here utilizes archival documents from the Presidential Libraries of George W. Bush and Barack H. Obama and conversations with directors and staff within the Partnership Centers established in the White House, federal agencies, and cabinet departments, to describe and analyze the implementation of faith-based service provision within structures of the state. This dissertation provides a discussion of how the implementation of faith-based service provision can be situated within theoretical approaches privatized service provision, as well as how this story clarifies some aspects of the current relationship between the state and religious organizations.
Keywords: Faith-based initiatives; Service provision; Faith-based service provision; Religion; State; Separation of church and state